2014
DOI: 10.1007/s11060-014-1417-2
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated stereotactic radiotherapy to the post-operative cavity for radioresistant and radiosensitive brain metastases

Abstract: Following surgical resection for brain metastases, fractionated stereotactic radiotherapy (FSRT) has been used as an alternative to single dose treatment for large cavities and to reduce risks of late toxicity. The purpose of this study was to evaluate the outcomes of patients treated with FSRT to the post-operative bed for both radioresistant and radiosensitive brain metastases. Between December 2009 and May 2013 a total of 65 patients with newly diagnosed brain metastases were treated with resection followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 25 publications
3
36
0
1
Order By: Relevance
“…This is in line with several other published series of fSRS which report one-year local control of 79-93%. [2, 4, 6-7]. Our median cavity size was similar to these series at 9.8 cc, and cavities up to 43 cc in size were treated safely.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This is in line with several other published series of fSRS which report one-year local control of 79-93%. [2, 4, 6-7]. Our median cavity size was similar to these series at 9.8 cc, and cavities up to 43 cc in size were treated safely.…”
Section: Discussionsupporting
confidence: 80%
“…Previous single fraction SRS series for intact brain metastases have shown that local control decreases with increasing tumor volume [16-17]. This has been noted in series of brain metastases treated with multimodality therapy, including fSRS [7]. Notably, the incidence of radionecrosis after single-fraction SRS has been shown to increase significantly when the volume receiving 12 Gy is > 8 cm 2  [18].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Parmi ces 18 % de cas, quatre ont été confirmés histologiquement avec une absence de cellules tumorales permettant d'écarter une récidive locale associée, soit au total 4,2 %. L'incidence de radionécrose en radiothérapie stéréo-taxique postopératoire varie entre 1,5 et 17,5 % selon les études (Tableau 3) [6][7][8][9][10][11]. Cet écart tient notamment à la variabilité des critères retenus dans la définition : critères cliniques et/ou histologiques et/ou radiologiques, auxquels s'ajoute la notion de délai d'apparition.…”
Section: Discussionunclassified
“…There is a wide range of reported data on the rate of actuarial radionecrosis. In recent studies with adequate follow-up, rates vary from as low as 1.5% [26] to as high 34% [19,25,27] The main risk factor of radionecrosis are total dose, maximum tumor diameter and treated volume [25,27,28].…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%